INTERVENSI: POLA KOMUNIKASI KELUARGA DALAM MENYELESAIKAN MASALAH PRIBADI DAN SOSIAL ANAK - Intan Nurfika Maulidya; Nurus Sa’adah (CONS-IEDU, 2023)
The purpose of this study was to determine the communication patterns that can be used and applied by parents in the family effectively. This research starts from the existence of various problems that arise in individuals consisting of personal and social problems that can occur from childhood to adulthood. The pattern of communication carried out by parents properly and appropriately will help individuals to prevent and even help various personal and social problems. The research method used is a literature review by taking ten journal articles that are relevant to the title and then reviewed and analyzed. The results showed that the communication patterns used by parents varied including free communication patterns, authoritarian communication patterns, democratic communication patterns. Communication is generally done face to face but as technology develops, it can be done by utilizing online communication media that are currently developing such as the use of smartphones